Reconstruction of Islamic Economic Law within the Modern Economic System: Between Normativity and Practice - Wahdini, Sri (El-kahfi | Journal of Islamic Economics, 2025)
This study aims to analyze and reconstruct Islamic economic law to ensure its relevance within the framework of modern economic systems shaped by globalization, digitalization, and the dynamics of free markets. The research addresses the gap between the normative values of Islamic law and the profit-oriented practices of contemporary economics. Employing a normative-empirical approach with a qualitative descriptive method, the study integrates textual analysis of the Qur’an, Hadith, and both classical and contemporary fiqh literature with empirical observations drawn from regulations, DSN-MUI fatwas, and practices of Islamic financial institutions and fintech in Indonesia. The findings reveal that the implementation of Islamic economic law still faces structural and epistemological challenges, particularly in maintaining the principles of justice and public welfare amid global market pressures. However, through a reconstructive framework grounded in maqāṣid al-sharī‘ah, Islamic economic law can be contextually actualized through product innovation, regulatory integration, and institutional strengthening. The study concludes that the reconstruction of Islamic economic law should not only adapt to technological and market developments but also play a transformative role in shaping an ethical, just, and sustainable economic system aligned with Islamic moral values